Identifying specific beliefs to target to improve restaurant employees’ intentions for performing three important food safety behaviors - Pilling, Valerie K.; Brannon, Laura A.; Shanklin, Carol W.; Howells, Amber D.; Roberts, Kevin R. (My University, 2008)
Current national food safety training programs appear ineffective at improving food safety practices in foodservice operations, given the substantial number of Americans affected by foodborne illnesses after eating in restaurants each year. The Theory of Planned Behavior (TpB) was used to identify important beliefs that may be targeted to improve foodservice employees' intentions for three food safety behaviors that have the most substantial affect on public health: hand washing, using thermometers, and proper handling of food contact surfaces. In a cross-sectional design, foodservice employees (n=190) across three midwestern states completed a survey assessing TpB components and knowledge for the three food safety behaviors. Multiple regression analyses were performed on the TpB components for each behavior. Independent-samples t tests identified TpB beliefs that discriminated between participants who absolutely intend to perform the behaviors and those with lower intention. Employees' attitudes were the one consistent predictor of intentions for performing all three behaviors. However, a unique combination of important predictors existed for each separate behavior. Interventions for improving employees' behavioral intentions for food safety should focus on TpB components that predict intentions for each behavior and should bring all employees' beliefs in line with those of the employees who already intend to perform the food safety behaviors. Registered dietitians; dietetic technicians, registered; and foodservice managers can use these results to enhance training sessions and motivational programs to improve employees' food safety behaviors. Results also assist these professionals in recognizing their responsibility for enforcing and providing adequate resources for proper food safety behaviors.
Keywords: Food safety; Theory of planned behavior; Employee attitudes; Restaurants; Foodservice